Why it felt wrong to remove the glass – investigating site and site-narratives at Regjeringskvartalet, Oslo, Norway - Airijoki, Oskar (2020)
The aim of this thesis is to find out in what ways site narratives emerge in the interaction between the human and the site, with Regjeringskvartalet (the site of the July 22, 2011 attack) in Oslo as case study. The purpose of the investigation is to shed light on how immaterial aspects can affect the understanding of the specific site. I argue that while immaterial aspects can affect design decisions in relation to the specific landscape, they are often ignored by the designer. The investigation and interpretation of the site are accomplished by a site visit applying the approach of the travelling transect in combination with Gadamer’s hermeneutic aesthetic theory. Resulting in six main parts systematically presenting various site-narrative. Thereafter, these narratives are discussed in relation to key concepts of landscape studies and Gadamer’s concepts of play, festival and symbol. The site-narratives and the following discussion exemplifies the extended thought process of a landscape designer in the early stages of a design project, showing that subjective and intersubjective aspects of site-thinking hold a significant role in the understanding of site. The paper ends with a reflection on how the knowledge obtained can be applied in design practice and future research, presenting the concept of photographic locality. However, the paper foremost presses the advantages of applying Gadamer’s spectatorial participation to design practice, indicating that designers themselves play an important role in the construction of site and therefore also in the understanding of site.